Analysis of student problem-solving errors based on Newman's theory in terms of learning interest and gender - Dewi Fatma Kumala; Anas Ma'ruf Annizar (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Errors often occurred when students solve mathematical problems solving, exceedingly when students are faced with contextual story problems. Newman's procedural error analysis classified errors in solved story problems into five categories: reading errors, encoding errors, transformation errors, comprehension errors, and processing skill errors. There were several factors on errors worked by students when solving problems, such as student interest in learning and gender differences. This study aims to describe the problem-solving errors of students, both men, and women, who have high, medium, and low interest in learning to solve story problems on SPLTV material. According to the Newman’s procedure. The research type is a qualitative approach with descriptive. And the research subjects were obtained by using a purposive sampling technique. The results of this study include 1) Students of high interest in learning and are making Encoding Errors, and Processing Skill Errors, while students with low interest in learning make Processing Skill Errors, Transformation Errors, and Encoding Errors. 2) Students with a great interest in learning and making encoding errors and processing skills errors. Students with low interest made Comprehension Errors, Encoding Errors, Processing Skill errors, and Transformation Errors.